2006
DOI: 10.1080/08035250600778636
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth in Sweden: What are the average lengths of hospital stay and the associated inpatient costs?

Abstract: The estimated lengths of stay and costs may serve as reference values for a Swedish setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 17 publications
3
45
0
Order By: Relevance
“…5,7,9,13,[17][18][19][20][21][22][23][24][25] None of the latter studies estimated the economic costs of LMPT birth from a societal perspective, however, with 11 studies limited to an estimation of hospital costs, 5,7,9,13,[19][20][21][22][23][24][25] and with two limited to an estimation of health and social services or public sector costs. 17,18 Moreover, these economic studies were either based on patient cohorts, recruited over a decade ago, 5,7,9,13,17,[19][20][21][22][23][24] or hypothetical cohorts simulated within models. 18, 25 The aim of this study was to estimate the economic costs during the first 2 years of life associated with LMPT birth in the context of a recent prospective population-based study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,7,9,13,[17][18][19][20][21][22][23][24][25] None of the latter studies estimated the economic costs of LMPT birth from a societal perspective, however, with 11 studies limited to an estimation of hospital costs, 5,7,9,13,[19][20][21][22][23][24][25] and with two limited to an estimation of health and social services or public sector costs. 17,18 Moreover, these economic studies were either based on patient cohorts, recruited over a decade ago, 5,7,9,13,17,[19][20][21][22][23][24] or hypothetical cohorts simulated within models. 18, 25 The aim of this study was to estimate the economic costs during the first 2 years of life associated with LMPT birth in the context of a recent prospective population-based study.…”
Section: Introductionmentioning
confidence: 99%
“…6 A recent structured review summarising published evidence on the economic consequences of LMPT birth, 6 found that ten studies, published between 1980 and 2011, focused on economic costs during the infant's initial hospitalisation, [7][8][9][10][11][12][13][14][15][16] whereas 13 studies reported economic costs in some form following the infant's initial hospitalisation. 5,7,9,13,[17][18][19][20][21][22][23][24][25] None of the latter studies estimated the economic costs of LMPT birth from a societal perspective, however, with 11 studies limited to an estimation of hospital costs, 5,7,9,13,[19][20][21][22][23][24][25] and with two limited to an estimation of health and social services or public sector costs. 17,18 Moreover, these economic studies were either based on patient cohorts, recruited over a decade ago, 5,7,9,13,17,[19][20][21]<...>…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] While most studies used population data some focused on admissions four to six weeks after discharge, 12,15,18 used inaccurate measures of gestational age 10,11,14,18 or had a large proportion of missing data. 9-11, 14, 16 We aimed to identify health care utilization and associated costs of infants with and without severe neonatal morbidity in the first year of life.…”
Section: Introductionmentioning
confidence: 99%
“…2013( , Curtis 2013. Empirical distributions on resource use from national estimates (Department of Health NHS Reference Costs 2013) and the existing literature (Ringborg, Berg et al 2006, Eddama, Petrou et al 2010 indicate that length of stay for the study population would not exceed one year. As a result, no discounting of hospital costs and clinical outcomes will be undertaken for the within-trial economic component.…”
Section: Nhs Reference Costs (Department Of Health Nhs Reference Costmentioning
confidence: 99%